Quantum Teaching Using TANDUR Syntax: A Complete Approach to Enhancing Cognitive, Affective, and Psychomotor Skills in Elementary Civic Education - Limsi Limsi; Iis Siti Aisyah; Lud Waluyo (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study:This study aims to analyze the effectiveness of TANDUR-based Quantum Teaching in improving student learning outcomes in the cognitive, affective, and psychomotor domains in Pancasila and Citizenship Education (PPKn) at the elementary school level. Methodology:This research used a quantitative approach with a quasi-experimental nonequivalent control group design. The instruments used include a written test, learning motivation questionnaire, and performance observation sheet. The sample consisted of 42 fifth-grade students divided into experimental and control groups. Main Findings:Students taught using the Quantum Teaching model scored higher in cognitive (78.12), affective (3.29), and psychomotor (80.10) domains than those in the control group. Statistical analysis showed significant differences (p < 0.05), with a dominant increase in learning motivation and social skills. Novelty/Originality of this study:This study presents the comprehensive application of TANDUR-based Quantum Teaching in citizenship education to foster character development through cultural diversity. It contributes a holistic, engaging, and contextual learning model aligned with the principles of the Independent Curriculum.